Review of 2010 financial security at Equity Silver Mine - Price, WA; Aziz, M; Bellefontaine, K (Mine Closure 2011: Sixth International Conference on Mine Closure, 2011)
The Equity Silver Mine operated between 1980 and 1994, producing silver, gold, and copper from three open pits and a small underground operation. Future liability is important at the site due to the environmental risk and high cost of treating acid rock drainage (ARD) produced by waste rock. As a condition of the Mines Act permit, British Columbia requires the provision of financial security. Security reviews have been held every five years since 1991. This paper outlines conclusions of the 2010 review and trends in costs over time.